New records of Sea Spiders (Arthropoda: Pycnogonida) for continental Portugal and notes on species distribution. Issue 1 (December 2016) - Esquete, Patricia; Rubal, Marcos; Veiga, Puri; Troncoso, Jesús
Abstract A sampling effort carried out in the Northern coast of Portugal revealed the presence of two species of sea spiders that are recorded for the first time in Portugal: Anoplodactylus angulatusand Ammothella longioculata. While A. angulatusis widespread along the North East Atlantic coast, A. longioculatais recorded for the first time outside of the Mediterranean Sea. Eight species were recorded in this survey, increasing the pycnogonid species list of Portugal to twenty-four. A species list of the Pycnogonids of continental Portugal including references and distribution is provided.